PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP MINAT BELAJAR (STUDI SURVEI DI SMA NEGERI 20 JAKARTA) - Ahmad Syahdi Al-Hazami; Firdaus; Iswan; Hasna Salsabila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the increasing use of social media among students, which has the potential to affect their interest in learning. Based on observations and interviews conducted at State Senior High School 20 in Jakarta, it was found that some students exhibited low interest in learning; among other things, they lacked focus during class and were more interested in non-academic activities, including the use of social media. This study aims to analyze the extent to which “social media use affects learning motivation” among students at State Senior High School 20 Jakarta. A quantitative method with a descriptive-correlational approach was employed, and data collection was conducted through observation, interviews, documentation, and the distribution of a Likert-scale questionnaire to students in this study. The study population consisted of 530 11th- and 12th-grade students at State High School 20 in Jakarta, with a sample size of 84 respondents determined using the Slovin formula with a 10% margin of error; the entire population was selected as the sample using purposive sampling. The data were analyzed using “Product-Moment Correlation (Pearson)” and “Simple Linear Regression”. The results of the study show that the correlation coefficient (rxy) between social media use (X) and interest in learning (Y) is 0.414, or 41.4%, which falls into the moderate or sufficient category. The results of the hypothesis test show that ro (0.414) is greater than rt at both the 5% (0.214) and 1% (0.280) significance levels; therefore, the Alternative Hypothesis (Ha) is accepted and the Null Hypothesis (Ho) is rejected. The coefficient of determination (R-squared) is 0.171, meaning that social media use contributes 17.1% to students’ interest in learning, while the remaining 82.9% is influenced by other factors such as teaching methods, family support, and self-motivation. Thus, it can be concluded that there is a significant positive effect of “social media use on learning interest” among students at SMA Negeri 20 Jakarta, although the effect is classified as moderate.